Analysis of Postures Towards Musculoskeletal Disorders Experienced By Batik Artisans of Sukamaju Giriloyo Yogyakarta (Public Health Perspective Journal, 2020)
Batik artisan tends to bend his neck while using a tool called canting to make batik fabrics for long hours (approximately 12 hours). Viewed from the health perspective, working in such position for long hours may cause abdominal muscles to be inelastic, bent spine and strained eye muscles. Health disorders are cummulative and if left alone for long period they will get worse, impair health and reduce work productivity. Batik artisans may produce batik fabrics in great amount but their long term health tends to be overlooked. Therefore, this study was aimed to analyze the effects of muscle overstretch (weight factor) and unnatural work posture (unnatural posture factor) on Sukamaju batik artisans in Giriloyu village, Yogyakarta. This study employed a mixed method of the regression test and descriptive explanation. The research results show that unnatural work posture and muscle overstretch (weight factor) may cause musculoskeletal disorders on written batik artisans of the Sukamaju batik artisan community in Giriloyo village.